Evaluasi Kualitas Steam Sebagai Game Launcher Berdasarkan Model ISO/IEC 9126 - Kurniawan, Hariz; Nelda, Lia; Widiatry, Widiatry (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Steam is one of the largest game distribution platforms with a substantial active user base, yet formal evaluations of its software quality using standardized assessment models remain limited. This study aims to assess the quality of Steam based on the ISO/IEC 9126 framework through a descriptive quantitative approach involving 20 active users. Data were collected using a questionnaire aligned with the six ISO/IEC 9126 characteristics and functional testing conducted with the black box method. The results indicate that functionality (4.10) and usability (4.05) received the highest scores, followed by reliability (3.75), which falls within the “good” category. Meanwhile, efficiency (3.20), maintainability (3.15), and portability (3.30) were rated as moderate. Functional testing supports these findings: six out of eight scenarios operated as expected, while two features cloud save and in-game overlay failed to function consistently. Overall, Steam performs well in its core functions but still requires improvements in feature stability and performance efficiency. These findings provide a comprehensive overview of Steam’s software quality from the user perspective and may serve as a reference for evaluating other digital game platforms.